Data visualization of violent crime analysis using plotting map technique / Adam Juhari M Wahi and Nur Asyira Naziron - M Wahi, Adam Juhari; Naziron, Nur Asyira (Faculty of Computer and Mathematical Sciences, 2021)
Crime can be concluded as an illegal act punishable by a state that can affect social, economic, health effects on someone and can reduce the quality of life of individuals or the community. Hence, Royale Malaysia Police (RMP) need to enforce laws to control the crime. In addition, some of the community established a society to eradicate the crime. However, there are some barriers in the community and Royale Malaysia Police such as the community has limits crime information and a lack of good quality of crime information. In addition, RMP has its own difficulty when it comes to investigating a crime, and they depend on the community's cooperation. As a solution, a data visualization of violent crime analysis model using plotting map technique that used New York’s violent crime dataset has been developed to helps the community and RMP to combat the crime. This model allows users to determine the trend, frequency, percentage, and locations violent crime occurred. This model follows the Cross Industry Standard Process methodology. The usability test has been conducted for the purpose of the ability to use by the user which are 26 out of 51 respondents highly agreed this model able to use by the user. The significance of this project is to help the community and RMP to combat the crime and reduce violent crime indirectly. In future, this model can be used to predict and determine the location of the next crime in the future.